Present status of fisheries in Turkey - Harlioglu, Ayse Gul (Springer, 2011)
Turkey's natural and ecological situations are very suitable for aquaculture. Turkey also has a wide variety of freshwater and marine species comprising trout, carp, sea bass, sea bream, turbot, mussel, crayfish, etc. The total production of fish and shellfish was 646,310 tons in 2008. The contribution of freshwater catch to total fishery production is relatively small. Capture fisheries production amounted to 494,124 tons whilst aquaculture production was 152,186 tons in the same year. In Turkey, Engraulis encrasicholus (anchovy) is the main caught sea fish species. Fisheries in the Black Sea are the most important fishery by far and show the greatest variations in total catch. Alburnus tarichii (a local species belonging to Cyprinidae) and Cyprinus carpio (the common carp) are the most important species caught from freshwaters. Aquaculture is going to play an increasingly important role in the Turkish economy, as fishery products are the only products of animal origin that can be exported to the EU. There has been a fast increase in the aquaculture production in Turkey with the implementation of scientific and technological modernization. For example, total aquaculture production for 1986 and 2008 was 3,075 and 152,186 tons, respectively. The percentage of aquaculture in total fish production has been rising every year. The ratio of cultured fish production to total fish production was 1.5% in 1990 s, 13.57% in 2000 and more than 20% in 2005. It was 23.55% in 2008. Trouts are the main cultured freshwater fish species. Race-ways and floating cages are employed in culture of trout. Carps are also important cultured freshwater fish species. Sea bass and gilthead sea bream are grown marine fish species. Floating cages, off-shore and earthen ponds are used for marine fish species culture. There has been an increase in fishery exports and imports in recent years. It was more than US$ 500 million in 2008, but that of 2004 was just over US$ 233 million. However, aquaculture production is still far away from the production targets and fisheries sector is not an important part of the economy at present.
Keywords: Aquaculture; Catch; Export; Fisheries; Import; Production; Turkey